Morphological-anatomical characterization and identification of Tomentella ectomycorrhizas. - Jakucs, Erzsébet; Eros-Honti, Zsolt (Mycorrhiza, 2008)
Over the last two decades, much information has been gathered on the ectomycorrhizal fungus community composition of plant associations of boreal, temperate, and tropical regions. Worldwide, Tomentella ectomycorrhizas (ECM) are often common and dominant in the mycorrhizosphere of coniferous and deciduous forests. They are present under different environmental conditions and associate with diverse plant hosts. Tomentella sporocarps, however, are rarely found aboveground, so Tomentella species are often missing from fungus community studies based on fruit-body presence. Tomentella is a resupinate genus of Thelephoraceae (Basidiomycota) forming black-brown, brown, yellow, or ochre ECM on the roots of gymnosperm and angiosperm trees, distinguished by typical morphological-anatomical characteristics (clamped hyphae, angular mantle, surface network, special rhizomorphs and cystidia). In this paper, we review the taxonomic position and morphological-anatomical characteristics of Tomentella ECM. A short summary of the microscopic features used for distinguishing tomentelloids during morphotyping and identification is presented in order to support molecular and ecological studies of ectomycorrhizal fungus communities.
Keywords: Anatomy; ECM; ectomycorrhiza; identification; morphology; Tomentella

Formation of Acutissimin A in red wine through the contact with cork - Gil, L; Pereira, C; Branco, P; Teixeira, A (JOURNAL INTERNATIONAL DES SCIENCES DE LA VIGNE ET DU VIN, 2006)
This study shows that when cork material gets in contact with wine, the elagitannins which exist in the cork material (namely one called vescalagin) react with the catechins present in the wine, producing, among others, Acutissimin A, which is an anti-tumoural agent about 250 times more potent than one of the most common anti-cancer drugs clinically used (VP-16). So, the contact of wine samples without the barrel winemaking stage (oak contact) was carried out with cork in order to determine the presence of Acutissimin A. After a contact time of about 30 min, 150 min and 6 days, Acutissimin A was detected in all samples containing cork. In the samples in which the contact was with oak wood, in our conditions, it was not possible to detect Acutissimin A.
Keywords: acutissimin A; Cork; HPLC/MS; identification; oak; wine

Formation of Acutissimin A in red wine through the contact with cork - Gil, L.; Pereira, C.; Branco, P.; Teixeira, A. (JOURNAL INTERNATIONAL DES SCIENCES DE LA VIGNE ET DU VIN, 2006)
This study shows that when cork material gets in contact with wine, the elagitannins which exist in the cork material (namely one called vescalagin) react with the catechins present in the wine, producing, among others, Acutissimin A, which is an anti-tumoural agent about 250 times more potent than one of the most common anti-cancer drugs clinically used (VP-16). So, the contact of wine samples without the barrel winemaking stage (oak contact) was carried out with cork in order to determine the presence of Acutissimin A. After a contact time of about 30 min, 150 min and 6 days, Acutissimin A was detected in all samples containing cork. In the samples in which the contact was with oak wood, in our conditions, it was not possible to detect Acutissimin A.
The following values have no corresponding Zotero field: pub-location: 42 RUE MARSAN, 33300 BORDEAUX, FRANCE publisher: VIGNE ET VIN PUBLICATIONS INT
Keywords: acutissimin A; Cork; HPLC/MS; identification; oak; wine

IDENTIFICACIÓN Y DESCRIPCIÓN DE LAS ECTOMICORRIZAS ZONA QUEMADA Y UNA ZONA SIN ALTERAR DEL CARRASCAL DE NAZAR ( NAVARRA ) - Román, D E; Miguel, M D E (Publicaciones de Biología, Universidad de Navarra, Serie Botánica, 2000)
Since 1998, a field study has been undertaken in a Quercus ilex L. subsp. ballota (Desf.) Samp. forest located in Nazar (Navarra, Spain). This study aims to establish a qualitative and quantitative comparison between the ectomycorrhizal morphotypes which have been collected, described and identified in a burned site and in a non- disturbed one within this forest. Thus, this study aims to contribute to the knowledge of the ectomycorrhizae associated with evergreen oak in field conditions, because most of the studies on evergreen oak ectomycorrhizae are related to truffle growing or artificial mycorrhization in the nursery.
Keywords: Ectomycorrhizae; fire; identification; morphology; Quercus ilex; Tuber melanosporum

IDENTIFICACIÓN Y DESCRIPCIÓN DE LAS ECTOMICORRIZAS ZONA QUEMADA Y UNA ZONA SIN ALTERAR DEL CARRASCAL DE NAZAR ( NAVARRA ) - Román, D. E.; Miguel, M. D. E. (Publicaciones de Biología, Universidad de Navarra, Serie Botánica, 2000)
Since 1998, a field study has been undertaken in a Quercus ilex L. subsp. ballota (Desf.) Samp. forest located in Nazar (Navarra, Spain). This study aims to establish a qualitative and quantitative comparison between the ectomycorrhizal morphotypes which have been collected, described and identified in a burned site and in a non- disturbed one within this forest. Thus, this study aims to contribute to the knowledge of the ectomycorrhizae associated with evergreen oak in field conditions, because most of the studies on evergreen oak ectomycorrhizae are related to truffle growing or artificial mycorrhization in the nursery.
Keywords: Ectomycorrhizae; fire; identification; morphology; Quercus ilex; Tuber melanosporum